Innovations In The Implementation of The Sapawarga Application In Taxpayer Administration - Elsa Selvia; Sri Wulandari; Hendri Suwarsono (Asian Journal of Social and Humanities, 2026)
The rapid advancement of information and communication technology has encouraged local governments to transform public services through digital innovation, particularly in taxpayer administration. Conventional administrative processes often face challenges, such as limited accessibility, lengthy procedures, and low levels of public participation, making the implementation of e-government necessary to improve service quality. This study aims to examine the implementation of the Sapawarga application in taxpayer administration at the Kuningan Regency SAMSAT Office, identify the challenges encountered during its implementation, and analyze government efforts to address these challenges. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The analysis was based on Richardus Eko Indrajit’s e-government framework, which consists of three dimensions: support, capacity, and value. The findings indicate that the Sapawarga application has improved taxpayer services by simplifying administrative processes, increasing efficiency, enhancing transparency, and enabling taxpayers to access services without directly visiting the SAMSAT office. However, several obstacles remain, including limited digital literacy, unstable internet infrastructure, technical system disruptions, and varying levels of user acceptance. The government has addressed these issues through public outreach, digital literacy programs, technical coordination, and the provision of alternative manual service options. In conclusion, the Sapawarga application represents a significant digital innovation that supports the modernization of taxpayer administration; however, continuous improvements in technological capacity and community readiness are required to ensure sustainable and equitable digital public services.